Brand equity and purchase decision of fast-moving consumer goods - Macias, Washington (2024)
This work analyses the influence of consumer-based brand equity on the purchase decision of fast-moving consumer goods in Ecuador. By estimating a partial least squares structural equation model and a logit model on a sample of 120 Ecuadorian university students, it was found that brand awareness with a strength of association is positively related to perceived quality, perceived quality influences attitudinal loyalty, and loyalty influences overall brand equity. In addition, after controlling for reference prices, overall brand equity has a direct positive effect on consumers' purchase decisions. For brand managers, the main implication of these findings is that investments to improve the dimensions of brand equity, with an emphasis on loyalty, is a relevant mechanism to increase sales and generate greater brand value.